Analyse comparative des destinations « neige » pyrénéennes - Laurent Botti; Olga Goncalves; Nicolas Peypoch (Revue de Géographie Alpine)
Destinations in general and ski resorts in particular face an intense competition which questioned competitiveness and call for analysis in terms of relative performance. This study considers that ski resorts’ competitiveness can be approach by ski-lift operators’ performance since it’s the primary attraction of the territory. Thus, ski resorts with comparable ski areas present in the same mountain, are in competition with each other. In this perspective, this paper proposes a comparative reading of Pyrenees ski resorts’ performance. The objective is to highlight the "best" snow mountain destinations and propose three directions to improve inefficient destinations’ practices. The first proposal is about ski area, the second one is about ski-lift operators’ human resources and finally on the political attractiveness of the territory.